The underlying factors and the probability of Peruvian sanitary and phytosanitary measures notifications of the agricultural sector to the WTO - Valverde Arevalo, Marcelo Alonso (Latin American Journal of Trade Policy, 2023)
Previously, a series of determinants of the sanitary and phytosanitary regulatory activity have been identified, such as scientific and legal capacities, national production, among others. Although the main determinants are oriented towards regulatory matters, it is not possible to discard that sanitary and phytosanitary measures are used as barriers to trade. In the case of Peru, being one of the WTO Members that has issued a major number of notifications, the underlying factors related to this kind of measure have not been previously analyzed. In this sense, through Probit and Logit models, it has been possible to identify the factors that affect the probability of Peruvian sanitary and phytosanitary notifications. The results indicate that, contrary to what was expected, in the Peruvian case, the increase in scientific and legal capacities would generate fewer sanitary measures. This would suggest that this country applies more measures than necessary, that could be used as barriers to trade.